A retrospective analysis of COVID-19 patients presented with vascular problems: a single center experience - Kolli, Kartik Datta; Pandian, Subrammaniyan Rathinavel; Gnanasekaran, Marun Raj; Ravichandran, Manoj Prabakar; Raja, Kamaraj; Ravipati, Ratnasri (International Surgery Journal, 2022)
Background: The aim of the study was to analyse clinical, biochemical parameters and treatment outcomes of COVID-19 patients with vascular disease. Methods: Retrospective analysis of data of COVID patients from May 2020 until July 2021. Results: 7 patients had arterial disease alone, 3 arterial and venous, 4 venous alone. Mean age of patients with arterial disease was 52. 80% were diabetic, 30% hypertensive, 30% thyroid disorders. 10% past CVA, 10% had past PAD history. 10% had history of tobacco consumption. 50% had severe and 20% had moderate COVID, 30% were post discharge. Mean duration of presentation was 20.1±18.6 days after COVID diagnosis; mean duration of symptoms 8.8±11.8 days. 50% femoro-popliteal segment and 20% iliac segment was involved. 10% each were subclavian, axillary and brachial occlusions. Mean±SD CRP, ESR and D-dimer at admission were 74.36±71.35, 97±38.5 and 1360±1538 respectively. 3 surgical, 1 medical intervention resulted in limb salvage in 4 patients (9.25 month follow up; 2 upper, 2 lower limb). 3 patients required trans-tibial or above amputations. Death occurred in 2 patients. The four patients with COVID induced VTE had no comorbidities, presented mean 5.75 days of symptom onset; COVID diagnosis mean 23.33 days prior. External iliac to popliteal vein was the most common pattern (75%). Mean CRP and ESR were lower than in the arterial cases. One patient underwent IVC filter placement and CDT; for another IVC filter was placed. All four were discharged uneventfully. Conclusions: Patients who developed arterial disease mostly had comorbidities, more severe COVID disease and higher mean inflammatory markers.